An Examination of Transition Models and Processes: Introduction of an Integrated Approach - Musamali, Kennedy (Advances in Social Sciences Research Journal, 2018)
A transition is the process initiated in response to a change event. It is characterized as an adaptive response to change over time marked by periods of disruption and distress. Many researchers have proposed models to facilitate transition management and successful adaptation. However, a review of the literature revealed while there were multiple transition models, many were limited in their scope and few offered a comprehensive approach to transition management. Furthermore, although studies revealed transitions were essential to successful adaptation, few studies examined transition as a central concept in normative change and adaptive processes. This paper reviews transition models and proposes an integrated framework with a comprehensive approach to transition management.